Impact of Visual Aids in Enhancing the Learning Process Case Study of students and teachers at Hamza Primary School in Sudan - Mohamed, Rashin Hasan. (IJRDO- Journal of Educational Research, 2022)
. This research explore the teachers opinions on the use of visual aids (e.g., pictures, animation videos, projectors and films) as a motivational tool in enhancing students’ attention in reading literary texts. To accomplish the aim of the research, the closed ended questionnaire was used to collect the required data. The targeted population for this research was the staffs and students of the public and private schools at Hamza Primary School in Sudan . In this research, the primary data was used for gathering information. The collected data is analyzed through the SPSS software and also data was represented in the percentage distribution of pie, line, and bar graphs. The analysis of the data indicated that the majority of the teachers and students had positive perceptions of the use of visual aids.